Oilseed Cake Flour Composition, Functional Properties and Antioxidant Potential as Effects of Sieving and Species Differences - Bárta, Jan; Bártová, Veronika; Jarošová, Markéta; Švajner, Josef; Smetana, Pavel; Kadlec, Jaromír; Filip, Vladimír; Kyselka, Jan; Berčíková, Markéta; Zdráhal, Zbyněk; Bjelková, Marie; Kozak, Marcin (Foods (Basel, Switzerland), 2021)
Oilseed cakes are produced as a by-product of oil pressing and are mostly used as feed. Their use for human consumption is due to the functional properties and benefits for human health. Herein, oilseed cake flours of eight species (flax, hemp, milk thistle, poppy, pumpkin, rapeseed, safflower, sunflower) were sieved into fractions above (A250) and below (B250) 250 µm. The chemical composition, SDS-PAGE profiles, colour, functional properties and antioxidant activities of these flours were evaluated. The B250 fractions were evaluated as being protein and ash rich, reaching crude protein and ash content ranging from 31.78% (milk thistle) to 57.47% (pumpkin) and from 5.0% (flax) to 11.19% (poppy), respectively. A high content of carbohydrates was found in the flours of hemp, milk thistle and safflower with a significant increase for the A250 fraction, with a subsequent relation to a high water holding capacity (WHC) for the A250 fraction (flax, poppy, pumpkin and sunflower). The A250 milk thistle flour was found to have the richest in polyphenols content (TPC) (40.89 mg GAE/g), with the highest antioxidant activity using an ABTS•+ assay (101.95 mg AAE/g). The A250 fraction for all the species exhibited lower lightness than the B250 fraction. The obtained results indicate that sieving oilseed flour with the aim to prepare flours with specific functional characteristics and composition is efficient only in combination with a particular species.
Keywords: protein; poppy; oilseed cake flour; milk thistle; flax; sunflower; rapeseed; antioxidant activity; hemp